E-IMPULSE BUYING: A REVIEW ON ITS HISTORY, CONSEQUENTIAL AND PROPOSITION INTEGRATIVE FRAMEWORK - de Oliveira, Abdinardo Moreira Barreto (2014)
The objective of this paper is presenting a framework on e-impulsing buying, considering the knowledge produced until now is not finished, we focus on the antecedents and consequences of this phenomenon. It was found that online store atmosphere is the main stimulus, prepared to attend the diverse behaviors regarding to the culture of the individuals (individualist or collectivist), and the positive emotions resulting from the store browsing are the main consequences. Depending on the experience lived in this flow; the costumer answer can be an impulse purchase (with a posteriori emotions manifested) or  planned purchases.